Real Estate Ownership Practices in the Hashemite Kingdom of Jordan and how to implement them in the Department of Land and Survey - Alzheimat, Samer Ahmed (Arab Journal for Sciences and Research Publishing, 2016)
The actions tanker Property Real Estate Hashemite Kingdom of Jordan are many and varied, including what produces two wills, such as compatibility (sale, donation, and swap, and the commandment, LV, moving, and exit, and secretion purpose of sale), some of which is algebraic without wills, such as compatibility (pre-emption, known as eminent domain expropriation, grab, and judicial decisions and judgments, and administrative decisions), Wait this research for detail and explain these behaviors and shed light on the procedures followed in the land registration departments to implement these actions.